Dark city - Proyas, Alex, 1963-; Mason, Andrew; Goyer, David S.; Dobbs, Lem.; Sewell, Rufus, 1967-; Sutherland, Kiefer, 1966-; Connelly, Jennifer; O'Brien, Richard, 1942-; Richardson, Ian, 1934-2007; Hurt, William ([United States] : New Line Home Entertainment, 2008)
When John Murdoch wakes with no memory at the scene of a grisly murder, he soon finds himself hunted by the police, a woman claiming to be his wife, and a mysterious group of pale men.
Originally produced as a motion picture in 1998.
Special features: expanded audiocommentaries by film critic Roger Ebert, director Alex Proyas, writers Lem Dobbs and David S. Goyer ; documentaries "Memories of Shell Beach" (making-of) and "Architecture of dreams" both introduced by Alex Proyas ; production gallery ; theatrical trailer.
Director of photography, Dariusz Wolski ; music, Trevor Jones
Rufus Sewell, Kiefer Sutherland, Jennifer Connelly, Richard O'Brien, Ian Richardson, William Hurt.
Not rated.
DVD, region 1; Dolby digital surround 5.1 EX, stereo surround , NTSC.
Keywords: Fugitives from justice -- Drama; Serial murders -- Drama; Serial murderers -- Drama; Amnesia -- Drama; Spanish language materials; Detective and mystery films; Feature films; Science fiction films